(untitled) (ҚазҰУ Хабаршысы. Дінтану сериясы, 2017)
The disclosure of the content of state policy in the sphere of religious relations can be considered from several aspects. First, better understanding of religious harmony in the public spiritual sphere. Se- condly, the study of human development as a representative of a particular culture of modern civilization. While one of the main factors in the formation of cultural and national identity is religion. Therefore, scientific and theoretical studies of active missionary activity of religious organizations that have a twenty-year history represent one of the urgent tasks. This will allow to regulate their interaction and predict the actions, religious relations in advance, and eradicate shortcomings. Pentecostals are the most active conductor of evangelism in Kazakhstan. The purpose of this article is to study the influence of appeals of this group on the public consciousness and prevent negative impact factors. The main issues of this article are the problems of preventing unfavorable factors associated with missionary activity.